Profil Fitokimia dan Aktivitas Antibakteri Kombucha Mesocarp Siwalan terhadap Propionibacterium acnes - Sejati, Wahyu Sukma; Sriwulan, Sriwulan; Nurfitria, Nia (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
Kombucha is a fermented probiotic drink made from sugar with the help of Symbiotic Consortium of Bacteria and Yeast (SCOBY). This study aims to determine the phytochemical profile and antibacterial activity of kombucha of Palmyra palm mesocarp (Borassus flabellifer) against Propionibacterium acnes, the main cause of skin acne. The research method used a complete randomised design (CRD) with 7 and 14 days of fermentation. Phytochemical test was conducted qualitatively to identify flavonoids, tannins, saponins, and alkaloid compounds. Meanwhile, the disc diffusion method was used to test the antibacterial activity of Palmyra palm mesocarp kombucha against P. acnes. The results showed that Palmyra palm mesocarp kombucha contained all the phytochemical compounds tested, with flavonoids only detected at 14 days fermentation and the alkaloid content was higher at 14 days fermentation. The highest antibacterial activity was obtained in 14-day fermented kombucha with an average inhibition zone diameter of 36.9 mm and categorized as very strong, equivalent to the positive control in the form of chloramphenicol. The flavonoid and alkaloid contents is thought to play a role in inhibiting bacterial growth. Thus, kombucha of Palmyra palm mesocarp has the potential as a natural antibacterial agent in the treatment of acne caused by P. acnes.